Regional development in the context of an innovation process - Natalia Irena Gust-Bardon (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2012)
The purpose of this paper is to identify main components and driving forces behind an innovation process in order to support regions in organising their endogenous innovation process. To that end, we study models of an innovation process and analyse the case of Sophia Antipolis. This theoretical study allows us to identify general inputs leading to creation of an endogenous innovation process in a region.
urn:nbn:de:0011-n-2139419
Keywords: 330; Innovation; Regionale Entwicklung; Endogener technischer Fortschritt; Theorie